EFFECT OF CELLULOSIC POLYMER ON PHYSICO MECHANICAL PROPERTIES OF SUPERPOROUS HYDROGEL OF AN ANTIHYPERTENSIVE DRUG AND DRUG RELEASE KINETICS FROM IT - Roy Biswas, Gopa; Roy, Debolina; Biswas Majee, Sutapa (International Journal of Applied Pharmaceutics, 2019)
Objective: Super porous hydrogels (SPHs), a novel drug delivery system can be developed to retain drugs in the gastric medium. The aim of the present investigation was to prepare superporous hydrogels (SPHs) of Atenolol to release the drug in sustained manner in the gastric environment and study the effect of two grades of hydroxyl methyl cellulose along with Carbopol 971p on the physico mechanical properties and drug release kinetics of the formulations. Methods: Superporous hydrogels of Atenolol were prepared with two grades of Hydroxy Propyl Methyl Cellulose (HPMC K100M and HPMC K15 M) along with Carbopol 971p the structural morphology of hydrogel was observed by Scanning Electron Microscopy. Study on Physico mechanical characteristics and drug release were done. Results: Scanning Electron microscopy studies of the formulations revealed the presence of large number of pores in different size ranges like 1 µm, 2 µm, 10 µm, confirming the formulations as superporous hydrogel. A correlation had been found between porosity, density and % swelling index. The drug release data from the formulations obeyed Higuchi and Korsmeyer-Peppas kinetics. Further, the data were fitted to the Kopcha model for confirming drug release by a combination of diffusion-controlled and chain relaxation–swelling mechanism. Conclusion: Among the six formulations, where HPMC K15 M and HPMC K100 M both were present, the gel became more hydrophobic and retarded the release of drug. From the drug release kinetics data, it can be concluded that the diffusion mechanism predominated the drug release process, leading to quasi diffusion and Fickian diffusion mechanism.